Coordinative regulation of ERAD and selective autophagy in plants. Issue 2 (5th August 2022) - Chen, Qian; Wu, Yaorong; Yu, Feifei; Xie, Qi
Abstract: Endoplasmic reticulum-associated degradation (ERAD) plays important roles in plant development, hormone signaling, and plant-environment stress interactions by promoting the clearance of certain proteins or soluble misfolded proteins through the ubiquitin–proteasome system. Selective autophagy is involved in the autophagic degradation of protein aggregates mediated by specific selective autophagy receptors. These two major degradation routes co-operate with each other to relieve the cytotoxicity caused by ER stress. In this review, we analyze ERAD and different types of autophagy, including nonselective macroautophagy and ubiquitin-dependent and ubiquitin-independent selective autophagy in plants, and specifically summarize the selective autophagy receptors characterized in plants. In addition to being a part of selective autophagy, ERAD components also serve as their cargos. Moreover, an ubiquitinated substrate can be delivered to two distinguishable degradation systems, while the underlying determinants remain elusive. These excellent findings suggest an interdependent but complicated relationship between ERAD and selective autophagy. According to this point, we propose several key issues that need to be addressed in the future.